IDENTIFICATION AND SELECTION OF DIGITAL CONTENT ELEMENTS IN THE COURSE “DIGITAL LITERACY" FOR A MOBILE APPLICATION - Issabaeva Д.; Rakhimzhanova Л.; Kultan Я.; Kakenbekova А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article is aimed at identifying the list and classification of digital content of the course "Digital Literacy" for inclusive education in primary school, as a result of the analysis of existing digital content. Based on international experience and internal research, not only the main problems of the digital content of the course "Digital Literacy" in inclusive education are identified, but ways to solve this problem are proposed. Based on the analysis of digital content, the suitability of sections of an electronic textbook for children with OOP is revealed. Using a survey and a questionnaire, some representations of parents and teachers were revealed. The main documents of the Republic of Kazakhstan were also analyzed in order to identify the positive and negative sides of this direction of teaching children with some restrictions. The existing digital content is analyzed and the list and classification of digital content elements for the course “Digital Literacy” for creating a mobile application for smartphones and tablets, taking into account the development of augmented reality (AR), are determined.